Utility of plasma cell‐free DNA in metastatic castration‐resistant prostate cancer. Issue 4 (7th June 2020) - Hamano, Itsuto; Hatakeyama, Shingo; Hamaya, Tomoko; Togashi, Kyo; Okamoto, Teppei; Yamamoto, Hayato; Yoneyama, Tohru; Yoneyama, Takahiro; Hashimoto, Yasuhiro; Ohyama, Chikara
Abstract : Introduction: Cell‐free DNA is suggested as a prognostic biomarker in metastatic castration‐resistant prostate cancer. However, it remains unknown which parameter of cell‐free DNA is correlated with the progression and prognosis of metastatic castration‐resistant prostate cancer. Case presentation: A 75‐year‐old man with newly diagnosed prostate cancer (serum prostate‐specific antigen 4891 ng/mL, Gleason score 4 + 5 = 9, cT3bN1M1) was referred to our department. He first received sequential hormonal therapies and was consequently diagnosed metastatic castration‐resistant prostate cancer 64 months after initial treatment. He underwent serial examinations of plasma cell‐free DNA, including concentration, androgen receptor amplification, TP53 point mutation, and PTEN loss. Only the cell‐free DNA concentration increased along with disease progression and declined after the administration of abiraterone and enzalutamide. Conclusion: This case presented that cell‐free DNA concentration was possibly correlated with response to castration‐resistant prostate cancer treatment and disease progression. Cell‐free DNA concentration was proposed as a potential prognostic biomarker of metastatic castration‐resistant prostate cancer.